Ramniwash Kumar (Farmer)- Rambad Village, Bihar India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Ramniwash Kumar is a young farmer from Rambad village in India. He explains in the video how he, due to the lack of water, has moved from maize and wheat to growing vegetables and fruits using conservation farming methods. These environmental friendly techniques were taught at the agriculture university and Ramniwash explains that he now has less work to do due to the effective conservational methods he is using in the field.